Menakar Kelayakan Desain Penelitian Studi Kasus Untuk Analisis Kebijakan - Prasetiyo; Trisnawati, Melinda; Mardiyanta, Antun (Universitas Airlangga, 2025)
As a research design, case studies have received a lot of criticism from practitioners. The most substantial criticism is the high potential for bias and its ability to generalize research findings. When associated with policy analysis, both things will have a major impact on the policy recommendations that will be produced. As is commonly known, effective, efficient, and applicable policies are the most important part in overcoming public problems. Therefore, choosing the right method in policy analysis is absolutely necessary to produce qualified policy recommendations. This article uses a literature study method to reveal the advantages, disadvantages, and opportunities for case studies to be used as a research design in policy analysis. Despite the criticism, the advantages of case study research design in providing in-depth and contextual insights and its flexibility in using data collection methods make it a valuable tool in policy analysis. With a careful approach and proper validation, case studies can make a significant contribution to the development of evidence-based policies. Keywords: bias, case study, generalization, public policy analysis, public policy